2004
DOI: 10.1097/00001888-200402000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent Skills in Internal Medicine Residency: How Are Residents Taught, and What Do They Learn?

Abstract: Explicit training in informed consent skills is urgently needed. Informal mentoring must be recognized as an important training method for informed consent and supported by appropriate teaching and evaluation strategies to ensure that resident-instructors do so effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 10 publications
3
29
0
2
Order By: Relevance
“…Moreover, it was seldom reported that the residents received assessment or feedback on their skills. 10 Our data collected from the New York State EM residency training programs is consistent with the existing research in that it suggests that many EM residents do not believe they are equipped with the information necessary to adequately follow informed consent guidelines. In addition, these data are suggestive of remarkable variability in the residents' informed consent practices.…”
Section: Variability In Informed Consent Practicessupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, it was seldom reported that the residents received assessment or feedback on their skills. 10 Our data collected from the New York State EM residency training programs is consistent with the existing research in that it suggests that many EM residents do not believe they are equipped with the information necessary to adequately follow informed consent guidelines. In addition, these data are suggestive of remarkable variability in the residents' informed consent practices.…”
Section: Variability In Informed Consent Practicessupporting
confidence: 80%
“…Based on Canadian residents' poor performance upon evaluation, McClean and Card called for ''the urgent need for enhanced teaching of informed consent skills in postgraduate training programs,'' as well as ''an effective strategy for regular formative feedback and accurate summative evalution.'' 10 Chadha and Repanos similarly noted that ''improvements in practice and knowledge should be possible with targeted educational sessions aimed at those involved in the consent process. '' 8 Our study also uncovered a need for formal informed consent training, and our results indicate that the EM residents often lacked the confidence in their knowledge of risks, benefits, and alternatives to properly relay this information to patients.…”
Section: Need For Trainingmentioning
confidence: 99%
“…General considerations such as test expense, accessibility, and degree of invasiveness may have influenced the resident-physicians' clinical recommendations. Additional factors may have contributed to the discordance including incomplete knowledge of currently endorsed guidelines (ie, failure to recognize colonoscopy as an acceptable screening option for average-risk patients), underdeveloped skills for obtaining informed consent, 21 physicians who may prefer FOBT as a CRC screening modality. 10,22 In terms of relative priorities for common preventive health services, breast cancer screening and hypertension screening were ranked higher than CRC screening by most residents in our survey.…”
Section: Discussionmentioning
confidence: 99%
“…Los médicos pueden realizar procedimientos sin obtener el consentimiento expreso, esto implica asumir el consentimiento que la mayoría de las personas podrían asentir (consentir) al momento de ser tratados en esta situación. informado de manera apropiada en el servicio de unidad de cuidado intensivo; los médicos señalan variabilidad en la interpretación de la necesidad del consentimiento informado y frecuentemente no tienen un entrenamiento formal; Rincón et al 11 recomiendan involucrar la enseñanza de la bioética en todos los niveles de pregrado, tanto del personal médico, como de los profesionales de la salud y particularmente en los que laboran en el servicio de unidad de cuidado intensivo, por la complejidad de las situaciones y de la toma de decisiones.…”
Section: Para Graciaunclassified